Current Topics in Ionic Liquid Crystals. Issue 1 (20th December 2021) - Kapernaum, Nadia; Lange, Alyna; Ebert, Max; Grunwald, Marco A.; Haege, Christian; Marino, Sebastian; Zens, Anna; Taubert, Andreas; Giesselmann, Frank; Laschat, Sabine
Abstract: Ionic liquid crystals (ILCs), that is, ionic liquids exhibiting mesomorphism, liquid crystalline phases, and anisotropic properties, have received intense attention in the past years. Among others, this is due to their special properties arising from the combination of properties stemming from ionic liquids and from liquid crystalline arrangements. Besides interesting fundamental aspects, ILCs have been claimed to have tremendous application potential that again arises from the combination of properties and architectures that are not accessible otherwise, or at least not accessible easily by other strategies. The current review highlights recent developments in ILC research, starting with some key fundamental aspects. Further subjects covered include the synthesis and variations of modern ILCs, including the specific tuning of their mesomorphic behavior. The review concludes with reflections on some applications that may be within reach for ILCs and finally highlights a few key challenges that must be overcome prior and during true commercialization of ILCs. Abstract : Recent developments in ionic liquid crystal (ILC) research are summarized in this Review article. The focus is on the synthesis of new and unusual ILCs, their mesomorphic behavior, and particularly rare ILC phases. Further topics include computer simulations and electrochemical features of ILCs. Finally, the article discusses the application potential of ILCs before concluding with a few observations of the difficulties and chances of ILC commercialization.